Buddhism, quantum theory and international relations: On the strength of the subject, the discontinuous relationality, and the world of contingency - Shimizu, Kosuke (Journal of International Political Theory, 2024)
This article is part of a forum on Karin Fierke’s book Snapshots from Home: Mind, Action and Strategy in an Uncertain World. In it, the importance of viewing international relations from the intersection of Buddhism and quantum theory is discussed. The ontological implication of Buddhism and quantum theory is extremely important in an uncertain world, and when we accept the uncertainty, we gain a new vision of contemporary world affairs. This is precisely where the gates of ethics open to us.